Phase transition dynamics of single optically trapped aqueous potassium carbonate particles. Issue 17 (13th April 2018) - Esat, Kıvanç; David, Grégory; Poulkas, Theodoros; Shein, Mikhail; Signorell, Ruth
Abstract : This study reveals that complex multiple processes occur during efflorescence and deliquescence in unsupported, submicron sized particles. Abstract : Fast dynamics (down to 10 ms) during exposure to changing relative humidity of single optically trapped K2 CO3 particles were observed in the submicron to micron size range with time-resolved broadband light scattering and Raman spectroscopy. The study shows that complex multiple processes accompany efflorescence and deliquescence of unsupported aerosol particles. Efflorescence can occur in a single process in less than 10 ms (prompt) or proceed via multiple successive processes (multistep) that can last up to more than 10 seconds. The efflorescence relative humidity lies in the range of 9 to 25%. Raman spectra of the effloresced particles reveal that the final state of the particle is independent of the pathway. Deliquescence cycles start with an initial uptake of water followed by multiple complex processes which end at the deliquescence relative humidity (44–50%). The study reveals that complex multiple processes during phase transitions are not limited to deposited particles where heterogeneous processes may occur or large particles in the upper micrometer size range as previously observed.